Traversing the Inner Seas: Contacts and Continuity in and around Scotland, the Hebrides, and the North of Ireland - Jamie Barnes; Christian Cooijmans; Clare Downham; Nicholas Evans; Ryan Foster; Ian Peter Grohse; Mark Hall; John Holliday; Arne Kruse; Alan Macniven; Alexandra Sanmark (Scottish Society for Northern Studies, 2017)
Throughout the medieval period, the ‘Inner Seas’ linking Scotland, the Hebrides, and the north of Ireland represented a confluence and crucible of identity. The region’s myriad islands served as stepping stones in a maritime network across which people, property, and perceptions travelled freely and purposefully. Encompassing three main themes, ten authors, and a multitude of interdisciplinary insights, this peer-reviewed volume represents some of the foremost research from the most recent residential conferences of the Scottish Society for Northern Studies, exploring the turbulent history and legacy of this interconnected seascape as both centre and periphery.